Sosialisasi Pentingnya Sarana Promosi Bagi Usaha AVAD Aksesoris Palembang - Seto, Agung Anggoro (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
One of the MSME actors in Palembang City which is engaged in making accessories is AVAD Accessories. Even though it has been operating for more than 5 years, this business still has several obstacles, which is why community service activities at AVAD Accessories are very necessary to support this business. This community service activity uses primary data sourced from interviews and direct observations with business actors as well as secondary data in the form of documents in the form of previous studies and literature studies related to the theme of community service activities. This activity uses three stages including pre-activities, core activities and final activities (evaluation). The results of this activity found that the AVAD Accessories business has several strengths such as product uniqueness and the availability of online sales services. Apart from the strength of AVAD Accessories, it also has several opportunities such as the availability of bazaars and business exhibitions to support product marketing and the availability of several people's business credits and credits for MSMEs as a source of additional capital. The AVAD Accessories business also has several weaknesses, such as not using adequate promotional means, not including a trademark, not having an adequate business location and not having a method for determining selling prices and financial recording. Several threat factors for the AVAD Accessories business include: There are several similar businesses or business competition in marketing locations and limited raw materials for some products.